THE RELATIONSHIP BETWEEN TEAM COHESION AND SPORTSMANSHIP AMONG VOLLEYBALL PLAYERS - Mahmoud, Khalid Shaker; Hammad, Barakat Abdel Hamza (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The aim of the research is to answer the following question: Is there a relationship between team cohesion and sportsmanship among volleyball players? To achieve this, the researcher used the Group Environment Questionnaire (GEQ) developed by Carron et al. (1985) to measure team cohesion, and a scale designed by Vallerand, Briere, Blanchard, and Provencher (1997) to assess sportsmanship tendencies. The two scales were applied to a sample of 116 volleyball players selected through a random sampling method. After data collection and statistical processing using the t-test and Pearson correlation coefficient, the following results were found: Volleyball players generally possess team cohesion. Volleyball players possess sportsmanship. A significant positive correlation was found between team cohesion and sportsmanship.